Pengaruh Disiplin Kerja dan Kompensasi Terhadap Loyalitas Karyawan PT. Aldimana Solusi Teknologi - T, Trihana; Syarif, Mahmud; Anggraini, Desy Tri (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Examining the impact of pay and work discipline on employee loyalty at PT Aldimana Solusi Teknologi is the aim of this research. The significance of preserving employee loyalty for the long-term viability and efficiency of business operations serves as the driving force behind this research. Three research topics comprise the primary emphasis of this study: (1) how work discipline affects employee loyalty; (2) how remuneration affects employee loyalty; and (3) how work discipline and compensation together affect employee loyalty. Among the data analysis techniques included in this quantitative research are multiple linear regression, validity testing, reliability testing, t-tests, F-tests, and the coefficient of determination. Software called SPSS v23 was used to help with the analysis. 35 participants who worked at PT Aldimana Solusi Teknologi provided information via questionnaires using a Likert scale, interviews, and observation. The results of the research show that employee loyalty is not significantly impacted by work discipline (t-calculated = 1.107 t-table = 2.037; p = 0.166 0.05). Additionally, it was shown that loyalty was significantly positively impacted by pay (t-calculated = 2.492 t-table = 2.037; p = 0.018 0.05). The combined effect of pay and work discipline on employee loyalty is 27.9%, according to the modified R-squared value of 0.279. This result implies that proper remuneration has a greater impact on gains in employee loyalty than work discipline.